PENGEMBANGAN MEDIA EDUKASI BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN CALISTUNG SISWA KELAS 2 SD - Hanifah Nurjanah; Isrok'atun; Rana Gustian Nugraha (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
The rapid development of the times, the flow of globalization is increasingly affecting all aspects of every aspect of human life, especially in the world of education. This is because the development of science and technology has played a very important role in the learning process of students at school. Therefore, research was conducted to answer challenges in understanding digital literacy which is still low with a focus on increasing calistung abilities. The study used the ADDIE method with descriptive-quantitative data analysis. The subject of the research trial was carried out to grade II elementary school students at SDN Cimekar and SDN Mekarwangi in Cileunyi District, Bandung Regency. Data was collected through field observation stages, written tests in the form of giving pretest & posttest questions to students and questionnaires to expert figures. In this study, it produced a percentage value of 92.86% in a very good category by media expert lecturers and a percentage value of 90% which had a good category even though revisions were delivered by material experts on the application display and material vocabulary. The pretest & posttest questions received an interpretation value of